INFLUENCE OF THE WTO'S AGREEMENT ON AGRICULTURE (AOA) POLICY ON INDONESIAN COFFEE IMPORTS 2007-2013 - Anshari, Andry; Aulina Lubis, Mia (Journal of Peasants' Rights, 2022)
As one of the policies issued by the World Trade Organization (WTO), the Agreement on Agriculture is an agricultural commodity agreement that binds all WTO member countries. As the fourth largest coffee producer globally, Indonesia must accept this policy as the exit to Indonesian coffee to various countries around the world. The study's findings get three things that influence agreement on agriculture (AoA) on Indonesian coffee imports. First, the opening of market access; Second, the reduction of domestic subsidies; Third, the removal of export subsidies. The method used in this study is qualitative-transcribed.